Fungi Endofit sebagai Biokontrol Patogen Utama Tanaman Cabai Merah (Uji Antagonisme dan Mekanisme Secara In Vitro) - Sri Nadia Commanechi; Wiwiek Harsonowati; Andree Saylendra; Endang Sulistyorini; Julio. E. R Rumbiak (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2024)
Endophytic fungi, particularly dark septate endophytes (DSE), have emerged as a promising and sustainable strategy for mitigating fungal pathogens in chili plants. Effective pathogen management is critical in chili production, as fungal infections can cause significant crop losses, reduce fruit quality, and decrease yield. While the use of endophytic fungi in plant protection has been explored in various crops, the potential of DSE as a biocontrol against fungal pathogens in chili plants remains unknown. The present study aimed to evaluate the effectiveness of DSE fungi as biological antagonists against significant pathogens that cause destructive diseases in chili plants, using in vitro trials. The study was conducted from December 2023 to March 2024 at the National Research and Innovation Agency (BRIN). A completely randomized design (CRD) was employed, with a single factor—DSE treatment. Three treatments included D0 (control), DSE 411, and DSE 471. Four pathogenic species were tested: Fusarium oxysporum (Fo), Phytophthora capsici (Py), Colletotrichum capsici (Cc), and Alternaria sp. (Alt). Inhibition rates (IR) were analyzed using Analysis of Variance (ANOVA), followed by the Least Significant Difference (LSD) test at a 5% significance level. The highest antagonistic activity was observed against C. capsici (Cc), with DSE 411 showing a mean value of IR of 77.54%, whereas DSE 471 exhibited a significantly higher IR of 90.26%. Macroscopic observations revealed the formation of clear zones around both DSE colonies, suggesting the mechanism of inhibition by antibiosis or the production of antifungal compounds. Microscopic analysis using scanning electron microscopy (SEM) revealed specific antagonistic mechanisms, including parasitism and competition, as key factors in pathogen suppression. These findings highlight the potential use of DSE fungi as effective biocontrol agents for managing major diseases in chili plants, offering a promising strategy for sustainable disease management and crop protection.